Is there an intermuscular relationship in voluntary activation capacities and contractile kinetics? - Hucteau, Elyse; Jubeau, Marc; Cornu, Christophe; Cattagni, Thomas (European journal of applied physiology, 2020)
Purpose The force-generating capacities of human skeletal muscles are interrelated, highlighting a common construct of limb strength. This study aimed to further determine whether there is an intermuscular relationship in maximal voluntary activation capacities and contractile kinetics of human muscles. Methods Twenty-six young healthy individuals participated in this study. Isometric maximal voluntary contraction (MVC) torque, voluntary activation level (VAL), and doublet twitch contractile kinetics (contraction time and half-relaxation time) evoked by a paired supramaximal peripheral nerve stimulation at 100 Hz were obtained in elbow flexors, knee extensors, plantar flexors and dorsiflexors of the dominant limb. Results Peak MVC torque had significant positive correlations between all muscle group pairs (all P values < 0.01). A significant positive correlation for VAL was found only between knee extensors and plantar flexors ( r = 0.60, P < 0.01). There were no significant correlations between all muscle group pairs for doublet twitch contraction time and doublet twitch half-relaxation time. Discussion These results show that there is a partial common construct of maximal voluntary activation capacities that only concerns muscle groups that have incomplete activation during MVC (i.e., knee extensors and plantar flexors). This suggests that the common construct of MVC strength between these two muscle groups is partly influenced by neural mechanisms. The lack of intermuscular relationship of contractile kinetics showed that there is no common construct of muscle contractile kinetics, as assessed in vivo by investigating the time-course of evoked doublet twitch contractions.